2021
DOI: 10.1523/jneurosci.0076-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

UNC-2 CaV2 Channel Localization at Presynaptic Active Zones Depends on UNC-10/RIM and SYD-2/Liprin-α inCaenorhabditis elegans

Abstract: Presynaptic active zone proteins couple calcium influx with synaptic vesicle exocytosis. However, the control of presynaptic calcium channel localization by active zone proteins is not completely understood. In a Caenorhabditis elegans (C. elegans) forward genetic screen, we find that UNC-10/RIM (Rab3-interacting molecule) and SYD-2/Liprin-a regulate presynaptic localization of UNC-2, the CaV2 channel ortholog. We further quantitatively analyzed live animals using endogenously GFP-tagged UNC-2 and active zone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…To rigorously distinguish these possibilities, further work is required. In a recent publication, RIMB-1 function was assessed with respect to its role in building the synaptic cytomatrix/DP and in anchoring CaV2 channels (Oh et al, 2021). These authors found a contribution of RIMB-1 and a larger effect of UNC-10/RIM mutations on CaV2/UNC-2 abundance at synapses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To rigorously distinguish these possibilities, further work is required. In a recent publication, RIMB-1 function was assessed with respect to its role in building the synaptic cytomatrix/DP and in anchoring CaV2 channels (Oh et al, 2021). These authors found a contribution of RIMB-1 and a larger effect of UNC-10/RIM mutations on CaV2/UNC-2 abundance at synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the tm5964 allele, which likely retains the N-terminal two thirds of the protein, exhibits a stronger phenotype than the complete deletion of RIMB-1. Also a recent publication reported normal distribution of UNC-2 VGCCs in the rimb-1(ce828) mutant (Oh et al, 2021). Possibly, in the absence of RIMB-1, where also other interactions of its N-terminus with unknown partners are absent, and/or due to compensatory changes, the ce828 animals show near wild type behavior.…”
Section: Rimb-1 Mutants Exhibit Reduced Cholinergic Transmissionmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the AZ proteins that mediate SV targeting, RIM tethers vesicles to release sites via its interaction with Rab3 (Wang et al, 1997;Betz et al, 2001;Koushika et al, 2001;Schoch et al, 2002;Han et al, 2011). RIM mutants have severely impaired evoked release accompanied by a dramatic reduction in SV docking (Gracheva et al, 2008;Han et al, 2011;Graf et al, 2012;Kushibiki et al, 2019;Oh et al, 2021). Together with the AZ protein SYD-2/Liprin, the C. elegans RIM homolog Unc10 forms filamentous projections that extend from the AZ to capture and tether Rab3 bound SVs at release sites (Gracheva et al, 2008;Stigloher et al, 2011).…”
Section: Snares Rabs and Rab Effectors Contribute To Target Specificity For Membrane Fusionmentioning
confidence: 99%
“…Several recent studies took the approach to ablate combinations of active zone protein families to analyze active zone assembly and function by eliminating redundant components (Acuna et al, 2016; Brockmann et al, 2020; Kushibiki et al, 2019; Oh et al, 2021; Tan et al, 2022; Wang et al, 2016; Zarebidaki et al, 2020). We simultaneously deleted RIM1, RIM2, ELKS1 and ELKS2, which resulted in a loss of RIM, ELKS, and Munc13, and in a strong decrease of Bassoon, Piccolo, and RIM-BP levels at active zones (Tan et al, 2022; Wang et al, 2016; Wong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%